Effects of environmental noise pollution towards school children - Abdullah S.; Fuad M.F.A.; Dom N.C.; Ahmed A.N.; Yusof K.M.K.K.; Zulkifli M.F.R.; Mansor A.A.; Mohd Napi N.N.L.; Ismail M. (Universiti Putra Malaysia Press, 2023)
Introduction: Noise, in particular, environmental noise is the undesirable sound produced by urbanization and industrialization process affecting human health such as hypertension, hearing loss, and sleep disturbances. We conducted a study analyzing noise pollution status and students and teachers perceptions of noise pollution at primary schools. Methods: The noise level is monitored during daytime (0700-2200 hours), simultaneously the questionnaires were distributed to students and teachers for subjective evaluation. Results: The evaluated equivalent noise level (LAeq) was 61.7 to 69.4 dBA on the school day and 62.2 to 62.3 dBA on the non-school day. For both school and non-school days, the Lmax is higher at schools located in the industrial area (77.0 dBA) rather than schools located in the residential area (74.5 dBA). Students agreed that the classroom was noisy (95%) and outside classroom noise that was heard by students is bell (43%), followed by traffic noise (26%). Additionally, the majority of teachers for both schools responded that road traffic (11.59%) is the source of outside school noise and most interference noise during the classes was produced by students (13.04%). Conclusion: Findings of this study are beneficial for policymakers and stakeholders in sense of noise pollution management at schools. 2021 UPM Press. All rights reserved.